Good teacher perceptions of students attending the pedagogical formation certificate program - Zeynep Ayvaz-Tuncel; İbrahim Tuncel (Institute of Advanced Engineering and Science, 2019)
A pedagogical formation certificate is required to become a teacher in secondary schools in Turkey. This certificate program, which is required to obtain in addition to a bachelor’s degree from any faculty other than the education faculties, aims at providing the knowledge, capabilities and attitudes required by the profession of teaching. This study aims at determining the perceptions of prospective teachers attending the pedagogical formation program about the properties of a good teacher. Data were collected using a survey comprising an open-ended question and content analysis was conducted to obtain the themes in this study, which adopted a descriptive method. Based on the properties of a good teacher, expressed by the prospective teachers, the themes “personal characteristics”, “enforcement of teaching process”, “establishing a democratic classroom environment” and “assessment and evaluation” are obtained.